Criminal Liability for Corruption of Bribery: Problems and Legal Reform - Rian Saputra; M Zaid; Muhammad Kurniawan Budi Wibowo; Willy Naresta Hanum; Devi Triasari (Journal of Law and Legal Reform, 2025)
This study aims to clarify the concerns of bribery and corruption within Indonesia’s legal framework for combating corruption, particularly with the duality in establishing legal norms that support criminal liability for bribery offenses. After identifying the concerns, this study aims to suggest ideas for amending bribery and corruption legislation based on legal certainty. This normative legal examination utilizes a legislative methodology and a comparative law framework. The study’s findings reveal that the Corruption Eradication Law, which regulates bribery offenses, engenders legal ambiguity in enforcing such crimes, as the legislators, namely the government and the Indonesian Parliament, have instituted provisions for bribery offenses that lack consistency. The manifestation of this phenomenon is mainly determined by the subjective assessments of law enforcement officials concerning the relevant statute. The subjective discretion of law enforcement officials in choosing relevant statutes may lead to the abuse of power concerning civil servants,state officials, and judges who accept bribes. To establish legal certainty, criminal liability for bribery may be achieved by amending Article 12(a) of the Corruption Eradication Law as follows: A civil servant or state official who accepts a gift or promise, with knowledge or reasonable suspicion that it is intended to induce him to act or refrain from acting contrary to his obligations, shall face a prison sentence of no less than 1 year and no more than 20 years, in addition to a penalty equivalent to five times the value of the bribe.